(untitled) (The International Journal for Scientific Research, 2024)
The study aimed to know the relationship between strategic planning and education outputs at the College of Administrative Sciences at Taif University in accordance with the Kingdom’s vision 2030, clarifying how Taif University applies strategic planning and benefiting from it in the educational outputs of the College of Administrative Sciences at Taif University in accordance with the Kingdom’s vision 2030, a statement of the impact of the dimensions of strategic planning (Vision, mission, strategic objectives, environment analysis) in the educational outcomes of the College of Administrative Sciences at Taif University in accordance with the Kingdom’s 2030 vision. The study used the descriptive analytical approach. The study reached a number of results, the most important of which is the existence of a statistically significant relationship at the level of statistical significance (α≤0.05) between strategic planning and education outputs at the College of Administrative Sciences at Taif University in accordance with the Kingdom’s Vision 2030, that the educational outputs of the College of Administrative Sciences at Taif University correspond to the vision of 2030. The study recommended many recommendations, including maintaining strategic planning at the College of Administrative Sciences at Taif University, encouraging the application of educational plans at the College of Administrative Sciences at Taif University and taking care of them, paying attention to the educational outputs of the College of Administrative Sciences at Taif University and considering them as one of the most important pillars of the labor market.